FASE EKONOMI KOREA SELATAN MENUJU TINGGAL LANDAS DAN FAKTOR-FAKTOR PENDUKUNGNYA - Azwirda Aziz; Hamdi Nur; Atik Budi Paryanti (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACT: Korea was one of the poorest countries in the world in the 1960s. However, by 1995 South Korea had become the 11th largest economy in the world. South Korea's phenomenal economic growth is also known as the